Ancestral journeys the peopling of Europe from the first venturers to the Vikings - Manco, Jean (Thames and Hudson, 2015)
"Who are the Europeans? Where did they come from? In recent years scientific advances have yielded a mass of new data, turning accepted ideas upside down. In this highly readable account, Jean Manco skilfully weaves the multiple strands of the very latest genetic evidence with archaeology, history and linguistics to produce a startling new history of Europe. Her fast-paced narrative is illustrated with numerous specially commissioned maps and diagrams showing the movements of people, the spread of languages and DNA distributions, as well as photographs and drawings. Completely up to date and unprecedented in the scope, breadth and depth of its research, this paradigm-shifting book paints a spirited portrait of a restless people that challenges our established ways of looking at Europe's past and its people. It will be of great interest to the growing number of people who want to trace their ancestry through DNA and understand what the results mean."--Back cover.